VALUATION PROBLEMS OF THE PENSION SYSTEM EFFICIENCY - Yulia A. German (Статистика и экономика)
The term “efficiency” is often used by professionals and scientists in the evaluation of pension system functioning. However, to date, common approaches to the determination of pension system efficiency aren’t developed and systematized. This article discusses the main methodological problems of evaluation the pension system efficiency the example of the Russian pension system and proposes criteria and indicators that can be used to carry out the relevant calculations.